Pohutukawa - Melbourne-Gibson, Kararaina (Te Kaharoa, 2020)
Ko Pohutukawa tōku ingoa, Pohutukawa is the name. My mum named me Pohutukawa because I was conceived under the biggest Pohutukawa tree in the world! Pretty mean aye? You would think she named me Pohutukawa because my red cheeks reminded her of those flowers, or because my eyes shine like stars - those damn stars. I live on the East Coast of New Zealand, in the small town of Te Araroa, where the biggest Pohutukawa tree also resides. A place where the birds can swim, the fish can fly, and where you can get an ice block at the shop for free! It’s also where my missus lives. She comes to visit me now and then, but I usually just follow that amateur around, sticking to her like a fly on a bloody teko; at least this teko is an East Coast teko. The East Coast provides only the best of everything! Best kina, best awa, best stags, and the best kōtiro. Have you met an East Coast girl? They’re pretty fly, they make me wanna touch the sky; they make me wanna pop their tops off with my lighter. My East Coast girl is as beautiful as Rehua on a hot summer night. What the fuck is this lovey-dovey shit? You know, I was never into stars until I met her; Kamaea Rora.